What do we know about the tax planning of German-based multinational firms? - Shafik Hebous; Alfons J. Weichenrieder (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
Research results confirm the existence of various forms of international tax planning by multinational firms. Prominent examples for firms employing tax avoidance strategies are Amazon, Google and Starbucks. Increasing availability of administrative data for Europe has enabled researchers to study behavioural responses of European multinationals to taxation. The present paper summarizes what we can learn from these recent studies in general and about German multinationals in particular.
Keywords: 330; taxation; foreign direct investment; multinational firms